2016
DOI: 10.1155/2016/3691523
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extruded Soy Protein on the Quality of Chinese Steamed Bread

Abstract: Five different extruded soy protein isolates (ESPIs) were obtained by extrusion and denoted by IVD1, IVD2, IVD3, IVD4, and IVD5. Then the SDS-PAGE results showed that the subunits of SPI decreased after extrusion, especially the subunits of 90.8, 32.8, and 31.3 kDa, whereas no isopeptide bond was formed. Although SPI improved both the development time (DT) and stability (S) of dough, ESPIs increasedSbut the DT decreased from 4.3 min to 1.8–2.0 min. Texture profile analysis (TPA) results showed that the hardnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
3
3
0
Order By: Relevance
“…Therefore, in contrast, SWP noodles also displayed a desirable yellow tinge, contributing to the improved surface appeal. Similar results for a* and b* variations after incorporation of the raw and modified protein (soy) were reported byDu et al (2016) for Chinese steamed bread and byKhatkar et al (2021) for instant noodles. The results of the sensory attributes are presented in Table…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, in contrast, SWP noodles also displayed a desirable yellow tinge, contributing to the improved surface appeal. Similar results for a* and b* variations after incorporation of the raw and modified protein (soy) were reported byDu et al (2016) for Chinese steamed bread and byKhatkar et al (2021) for instant noodles. The results of the sensory attributes are presented in Table…”
supporting
confidence: 84%
“…Consequently, more water was required to hydrate and flowable the material before mixing. Khatkar et al (2021) and Du et al (2016) also reported similar observation during dough handling for restructured soy protein and extruded SP isolates, respectively. This could be because proteins are amphiphilic, and modification exposes hydrophobic groups, encouraging disulfide and crosslink bonding for gluten.…”
Section: Dough Machinabilitysupporting
confidence: 62%
“…Wheat-flour foods have a huge amount of consumption in China and around the world. In recent years, many exogenous materials such as wheat bran, black tea, purple sweet potato powder, banana pulp and peel, seed powder, fiber, non-starch polysaccharides and soy protein, have been added into noodles, bread and steamed bread to improve their nutritional and functional properties (Du et al, 2016;Fu, Chang, & Shiau, 2015;Gökşen & Ekiz, 2016;Li, Zhu, Guo, Brijs, & Zhou, 2014;Ramli, Alkarkhi, Shin, Min-Tze, & Easa, 2009;Santiago et al, 2016;Sim, Aziah, & Cheng, 2015;Song, Zhu, Pei, Ai, & Chen, 2013;Wandee et al, 2015;Zhu, Sakulnak, & Wang, 2016). Dough modulation is the basis for preparing most wheat-flour foods.…”
Section: Introductionmentioning
confidence: 99%
“…The study concludes that the small size of the rice starch granules helped in the creation of a more continuous protein matrix, producing doughs with higher peak stress (0.56 ± 0.11 MPa) when compared to maize (0.39 ± 0.08 MPa) and potato starch (0.24 ± 0.09 MPa), both of which produce larger starch granules. This study can also be considered a mechanical treatment since shearing during extrusion can produce new non-covalent interactions between proteins and other dough components [ 93 ].…”
Section: Protein Modification In Gluten-free Doughmentioning
confidence: 99%